(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
First Asphalt concrete consists of Aggregates, filler and Bitumen. Generally in practice, cement, limestone and stone dust filler materials are used in Asphalt pavement construction work. The recycled rubber produced from automotive and truck tires called crumb rubber is also being used in bituminous pavement construction. Ground granulated blast furnace slag (GGBFS) is a by-product of iron/steel industry which can also be used as a filler material in Asphalt concrete. In the present study an attempt is made to asses and evaluate the effects of repeated freezing and thawing on Crumb Rubber Modified Bitumen (CRMB) using (GGBFS) as a filler material and compare the test results with the samples using OPC as filler by carrying out experimental investigation such as Marshall mix design test to evaluate stability, flow and void characteristics of samples. The Asphalt concrete samples were made using Bituminous concrete (Grade II) with bitumen content fixed at 5.4% From Marshall mix design and crumb rubber content fixed at 15% by weight of the binder based on literature survey. The amount of (GGBFS) used as filler material is fixed at 4% on the basis of literature survey. Moreover the focus has been on exploring options to enhance the condition of pavements and save subsequent maintenance and frequent overlaying expenses in cold regions where the asphalt pavements undergo deterioration due to seasonal freezing thawing.